Perancangan Konstruksi Main Girder pada Overhead Crane Single Girder SWL 2 Ton untuk Laboratorium Outboard Engine di Politeknik Perkapalan Negeri Surabaya - Maulana Tanziilal Aziizir Rohiim; Tri Andi Setiawan; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
In this study, the main girder overhead crane construction design with a SWL capacity of 2 tons was carried out for the outboard engine laboratory at PPNS. The design is continued with the analysis of the strength of the construction made to calculate the maximum stress, and deflection. The analysis process will use the FEM (fenite element methods) approach using FUSION 360 software. Comparing the simulation results is carried out on the resulting stress values. From the results of the design and analysis, it is found that the dimensions of the main girder have met the requirements.